Pengaruh Citra Merek dan Kualitas Pelayanan terhadap Kepuasan Konsumen pada J&T Express Kota Batam - Bella Cilcilia Putri; Endang Sutrisna (Departement of Mathematics Education, 2023)
This study aims to determine the effect of brand image and service quality on consumer satisfaction. The method used in this research is descriptive and quantitative statistics, the source of the data in this study comes from primary data obtained through the process of distributing questionnaires which are then carried out statistical tests with the SPSS program and secondary data using target data and actual sales of J&T Express Botania 2 shipping services Batam City for the 2017-2021 period. Samples were taken as many as 100 respondents using accidental sampling technique. Data analysis technique used is quantitative analysis using validity test, reliability test and simple and multiple linear regression analysis. The test results in this study indicate that partially the brand image variable (X1) has a positive and significant effect on consumer satisfaction (Y). Partially, the service quality variable (X2) has a positive and significant effect on customer satisfaction (Y). And simultaneously brand image (X1) and service quality (X2) have a positive and significant effect on customer satisfaction (Y).